Mechanisms of Unrest and Eruption at Persistently Restless Volcanoes: Insights From the 2015 Eruption of Telica Volcano, Nicaragua. (21st August 2019) - Roman, Diana C.; LaFemina, Peter C.; Bussard, Rebecca; Stephens, Kirsten; Wauthier, Christelle; Higgins, Machel; Feineman, Maureen; Arellano, Santiago; de Moor, J. Maarten; Avard, Geoffroy; Cruz, Maria Martinez; Burton, Mike; et al.
Abstract: Many of Earth's volcanoes experience well‐defined states of "quiescence" and "unrest, " with unrest occasionally culminating in eruption. Some volcanoes, however, experience an unusually protracted (i.e., decades‐long) period of noneruptive unrest and are thus categorized as "persistently restless volcanoes" (PRVs). The processes that drive persistently restless volcanism are poorly understood, as our knowledge of PRVs is currently based on a small number of case studies. Here we examine multidisciplinary observations of the 2015 eruptive episode at Telica Volcano, Nicaragua, in the context of its long‐term behavior. We suggest that the latter phases of the 2015 eruption were ultimately driven by destabilization of its shallow magma reservoir. Based on previous geodetic‐seismic studies of Telica (Geirsson et al., 2014, https://doi.org/10.1016/j.jvolgeores.2013.11.009 ; Rodgers et al., 2013, https://doi.org/10.1016/j.jvolgeores.2013.08.010 and 2015, https://doi.org/10.1016/j.jvolgeores.2014.11.012 ) and on multiparameter observations at Telica over a 7‐year period, we propose that three distinct states of unrest occur at Telica over decadal timescales: a stable open state involving steady conduit convection and two distinct "unstable" states that may lead to eruptions. In the "weak sealing" state, phreatic explosions result from steady conduit convection underlying a weak seal. In the "destabilized" state, destabilization of the top of the convecting magma in the conduit leads to rapid accumulation of high pressures leading to strong/impulsive phreatomagmatic explosions. Our observations and interpretations suggest that continuous seismic, ground‐based deformation, gas emission, and thermal monitoring and interpretation of these data within a paradigm of sustained conduit convection modulated by episodes of sealing and destabilization of shallow magma reservoirs may allow robust forecasting of eruption potential, energy, and duration at Telica and similar PRVs worldwide. Key Points: Persistently restless volcanoes experience multiple distinct stable and unstable states of unrest, some of which lead to explosions The latter phases of the 2015 eruptive episode at Telica Volcano were ultimately driven by destabilization of its shallow magma reservoir Multiparameter monitoring may allow robust forecasting of eruption potential, energy, and duration at Telica and similar PRVs worldwide